ANALISIS KECEMASAN MATEMATIS DITINJAU DARI KOGNITIF PESERTA DIDIK DALAM MENGERJAKAN SOAL HIGHER ORDER THINKING SKILLS (HOTS) MATEMATIS - Rahayu, Azzahra Sri; Yenti, Isra Nurmai; Sari, Tasya Laura Permata (UIN Imam Bonjol Padang, 2024)
This research aims to explore students' mathematical anxiety in solving mathematical Higher Order Thinking Skills (HOTS) problems. This research was motivated by the high mathematical anxiety of students and a curriculum that requires students to have various abilities and skills in the 21st century. All of these abilities and skills are contained in the HOTS mathematics questions. This research is a qualitative descriptive research. The research subjects were students in class VII.1 of SMP Negeri 1 Kec. Kapur IX was selected using a purposive sampling technique. The researcher is the key instrument, while the HOTS mathematics test which contains two description questions, a mathematical anxiety questionnaire, and an interview guide are the supporting instruments of this research. The stages of data analysis are reduction, presentation in narrative form, and conclusion. This research found that students whose mathematical anxiety was dominant in the cognitive aspect (way of thinking) had different answer results to HOTS mathematics questions. Students feel less confident, don't concentrate, and feel unsure of their abilities in working on HOTS mathematics questions.